Microarchitectural aspects of increased bone fragility in individuals with type 2 diabetes: N/A - Ćirović, Aleksandar; Milovanović, Petar (Medicinski podmladak, 2023)
Type 2 diabetes (T2DM) is a common noncommunicable disease that represents one of the leading public health problems worldwide. An increased risk of fractures, particularly fractures of the femoral neck, has been recognized as one of the complications of diabetes. However, fracture risk assessment in individuals with T2DM remains challenging because the results of densitometric measurements are unreliable in these individuals. Namely, individuals with T2DM often have a T-score that is identical to or better than that in individuals without T2DM. Various research groups have conducted basic and clinical analyses of cortical or trabecular microarchitecture of the distal radius, tibia, or femoral neck. The methodology and results of these studies are heterogeneous, and a definitive conclusion on the state of bone microarchitecture in individuals with T2DM is still lacking. Therefore, the aim of our study was to summarize the results of previously conducted studies of bone microarchitecture in individuals with T2DM and draw conclusions on the state of bone microarchitecture in individuals with T2DM. It is difficult to observe any changes in trabecular bone microarchitecture unless individuals with T2DM have developed microvascular or macrovascular complications; in that case, the results of the studies indicate that trabecular bone microarchitecture is significantly worse than that in individuals without T2DM.
Keywords: diabetes; trabecular microarchitecture; fracture; vascular complications